Historical of Forensic Medicine (Revista da Faculdade de Direito, Universidade de São Paulo, 2010)
The assertive “there is no way to understand how exquisite the forensic medicine without first analyzing your history” already demonstrates p purpose of this matter that traces the trajectory of this fascinating Chair in the right area, since antiquity in times of priests who ruled in the manner of divine strength and evocation, passing by the Egyptian universe when corpses were stuffed into complex rituals, arousing attention of archaeologists from all over the world, in primate to understand and decipher the history of mankind. And corpses, in Egypt, were considered sacred and are still, today. The story continues narrating about the laws of Menes, Hammurabi’s code that will be the oldest criminal legislation that has news, the law of the XII boards, of the Roman Empire, other add-ons added: the history of forensic medicine.